Harmonious Communication in the Household: Tafsir Qs Al Hujurat And An-Nisa - Sari, Iftah Kurnia; Mahmud Abdullah, Ahmad Belo (-, 2025)
This study aims to provide an in-depth understanding of the concept of harmonious communication within the family based on the values of the Qur'an, particularly those contained in Surah Al-Hujurat and An-Nisa. In Islamic teachings, the family is the primary foundation for building a harmonious and religious society. One of the key elements in creating a family that is sakinah, mawaddah, and rahmah is effective communication among family members, especially between husband and wife. Poor communication often triggers conflicts within the household, and in some cases, leads to divorce. This study employs a normative legal research method with a statute approach. The method used is library research, which involves collecting and analyzing data from various Islamic literature, including Qur'anic exegesis and Islamic law books. Surah Al-Hujurat and An-Nisa serve as the primary sources, analyzed through classical and contemporary exegesis to explore Islamic communication values. The results of the study indicate that communication based on Qur'anic values, such as honesty, mutual respect, and responsibility, plays a significant role in maintaining family harmony. The discussion in this study emphasizes that these communication principles can prevent prolonged conflicts, strengthen emotional bonds among family members, and serve as solutions in addressing the challenges of family life.